LENTIL GERMINATION AS A SOURCE OF PREBIOTIC TO STUDY THEIR EFFECTS IN COMMON CARP PERFORMANCE, PHYSIOBIOLOGICAL, BLOOD, HEALTH AND PROXIMATE ANALYSIS - N. Mohialddin Abdulrahman; E. Tayar Sadeeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The experiment was conducted at the University of Duhok's College of Agricultural Sciences. The study used a completely randomized design with four treatment groups, three repetitions, and ten fish per replication in twelve plastic tanks (70 L), each tank receiving proper continuous aeration and cleaning on a daily basis. Positive Control (T2) was higher significantly in each of the Weight Gain, Daily Weight Gain, Relative Growth Rate, Feed Efficiency Ratio, Protein Efficiency Ratio, Fat Efficiency Ratio, Hepatic Index, Kidney Index, Lymphocytes (10^9/dl), Monocytes (10^9/dl), and Granulocytes (10^9/dl). T3 with 25 gm germinated lentil /kg was higher significantly in Intestine Length- Weight Index and MCHC (%). T4 with 50 gm germinated lentil /kg increase significantly Intestine Length- Length Index, WBC (10^9/dl), PLT (10^ 9/L), Cholesterol mg/dl, and LDL mg/dl. Negative Control (T1) and 25 gm germinated lentil /kg (T3) were higher significantly in Feed Conversion Ratio, Triglyceride mg/dl, and HDL mg/dl. T2 and T3 increased significantly RBC (10^ 12/L). All treatments as compared to control enhances Ether extract (Oil) (%), Crude protein (%), Weight without viscera and Head, and Spleen Index.